Pembuatan Marinasi Udang Swallow (Penaeus merguiensis) Dengan Pengolahan Bumbu Yang Berbeda - Hermanto; Muhajjir; Ridhayani Lubis, Ahyani; Diana, Ayu (Jurnal Online Pertanian Tropik, 2022)
Shrimp is one of the most popular types of seafood. Processed in any way, such as fried, steamed, baked, or made into a salad, shrimp is still delicious to eat. Marinating is the process of soaking meat in a marinade, before it is further processed. This study aims to determine the level of consumer acceptance of the manufacture of swallow shrimp marinade with different spice processing based on the hedonic test and to determine the nutritional content of the best value from the hedonic test of shrimp marinade with different spice processing. The shrimp marinade research method was divided into three stages. The first stage is sample and material preparation, the second stage is making shrimp marinade and the third stage is hedonic and proximate testing of the marinade. The research treatment design used was a completely randomized design (CRD). The results of the study obtained the best value from the hedonic test of shrimp marinade with the criteria of appearance = 6.30, aroma = 6.46, texture = 6.46 and taste = 5.85. The results of the test of the nutritional content of the marinade were based on the best value of the hedonic test results, namely water content = 73.61%, ash content = 5.45%, fat content = 0.31, protein content 19.26% and carbohydrate content 1.38.Keywords: Swallowed shrimp, Marinated, Hedonic Test, Proximate Test